2019
DOI: 10.1093/neuonc/noz235
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular subgrouping of atypical teratoid/rhabdoid tumors—a reinvestigation and current consensus

Abstract: Background Atypical teratoid/rhabdoid tumors (ATRTs) are known to exhibit molecular and clinical heterogeneity even though SMARCB1 inactivation is the sole recurrent genetic event present in nearly all cases. Indeed, recent studies demonstrated 3 molecular subgroups of ATRTs that are genetically, epigenetically, and clinically distinct. As these studies included different numbers of tumors, various subgrouping techniques, and naming, an international working group sought to align previous fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(204 citation statements)
references
References 39 publications
10
194
0
Order By: Relevance
“…Significant differences in viability were observed between ATRT-06 as compared to NSC (p < 0.05), and between ATRT-06 and ATRT-05 compared to HEK-293 (p < 0.001), at 1 µM 4SC-202 treatment, according to paired two-tailed t-tests (Figure 2a,b). Recent studies examining the molecular subtyping of ATRT tumors indicate that ATRT-05 is most closely correlated with Group 1 ATRT (neurogenic, ATRT-SHH) and ATRT-06 with Group 2 ATRT (mesenchymal, ATRT-MYC) [31,32]. Additionally, in a spheroid model, treatment with 56 nM 4SC-202 significantly decreased spheroid growth when compared to a vehicle treatment with 0.02% DMSO ( Figure S2).…”
Section: Sc-202 Is Cytotoxic and Cytostatic To Atrt In Two-and Threementioning
confidence: 89%
See 1 more Smart Citation
“…Significant differences in viability were observed between ATRT-06 as compared to NSC (p < 0.05), and between ATRT-06 and ATRT-05 compared to HEK-293 (p < 0.001), at 1 µM 4SC-202 treatment, according to paired two-tailed t-tests (Figure 2a,b). Recent studies examining the molecular subtyping of ATRT tumors indicate that ATRT-05 is most closely correlated with Group 1 ATRT (neurogenic, ATRT-SHH) and ATRT-06 with Group 2 ATRT (mesenchymal, ATRT-MYC) [31,32]. Additionally, in a spheroid model, treatment with 56 nM 4SC-202 significantly decreased spheroid growth when compared to a vehicle treatment with 0.02% DMSO ( Figure S2).…”
Section: Sc-202 Is Cytotoxic and Cytostatic To Atrt In Two-and Threementioning
confidence: 89%
“…FOXM1 was also identified as the downstream target of MYC in prostate cancer [74]. This relationship between MYC and FOXM1 is of particular interest since MYC is one of the key distinguishing features of the ATRT-MYC type, and the cell line used for the single-cell RNA-sequencing experiment has recently been classified as ATRT-MYC type [31,32]. Inhibition of MYC has been demonstrated to decrease pluripotency-related pathways and tumor self-renewal [73,75], and is altered by HDACi's.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that loss of SMARCB4 is critical in ATRT development, but less frequent [115]. ATRTs encompass three epigenetic subgroups with distinct genomic profiles and SMARCB1 genotypes [116]. ATRT-TYR tumors are more common in the infratentorial regions, ATRT-MYC tumors are commonly seen in the supratentorial area, and ATRT-SHH tumors are seen in both infraand supra-tentorial areas.…”
Section: Atypical Teratoid/rhabdoid Tumormentioning
confidence: 96%
“…Oncology Group ACNS0333 study, with some suggestion that ATRT-SHH benefit from high-dose chemotherapy approaches and ATRT-TYR benefit from radiotherapy [116,[118][119][120][121]. The EZH2 inhibitor tazemetostat is a rational approach to target the SWI/SNF complex and is being investigated in upcoming clinical trials; however, there is a paucity of early phase human data at the present time [122].…”
Section: Molecular Classification Of Pediatric Brain Tumors 257mentioning
confidence: 99%
“…In spite of their consistent homogeneity on the genetic level, ATRTs display a remarkable epigenetic and transcriptional heterogeneity (Johann et al, 2016;Torchia et al, 2016). Based on these studies, ATRTs are currently segregated into three molecular subgroups: ATRT-SHH (formerly group 1), ATRT-TYR (group 2A), and ATRT-MYC (group 2B) (Ho et al, 2020). Whereas these distinct molecular profiles clearly correlate with clinical features, such as patient age and tumor location, it remains elusive if these molecular subgroups also enable molecular-driven therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%